Renal Adenomas: Pathological Differential Diagnosis with Malignant Tumors. (8th October 2008) - Algaba, F.
Abstract : The renal adenomas can be confused by imaging diagnosis with malignant renal tumors, but there are also real biological dilemmas to determine their behavior. The consensus decisions are the following. (1) The adenoma of clear cells is not accepted, instead it is considered that all the clear-cell tumors are carcinomas, with greater or lesser aggressiveness. (2) Among the papillary neoplasms the WHO 2004 renal cell tumors classification are considered as papillary adenomas tumors with a maximum diameter of 5 mm and may represent a continuum biological process to papillary renal cell carcinoma. The papillary adenomas associated with End-kidney and/or acquired cystic disease may have a different pathogenesis. (3) To consider a tumor as an oncocytoma the size is not important, only the cytological features, microscopic, ultrastructural, and immunohistochemically can help, but some chromosomal observations introduce some questions about its relation with the chromophobe renal cell carcinoma. (4) Finally, the metanephric adenoma, a tumor with some morphological similarity with the nephroblastoma must be considered in the renal adenomas diagnosis.